What Are the Priorities of Bureaucrats? Evidence from Conjoint Experiments with Procurement Officials - Janne Tukiainen; Sebastian Blesse; Albrecht Bohne; Leonardo M. Giuffrida; Jan Jääskeläinen; Ari Luukinen; Antti Sieppi (Center for Economic Studies and ifo Institute (CESifo), 2023)
While effective bureaucracy is crucial for state capacity, its decision-making remains a black box. We elicit preferences of 900+ real-world public procurement officials in Finland and Germany. This is an important pursuit as they report having sizeable discretion and minimal extrinsic incentives. Through conjoint experiments, we identify the relative importance of multiple features of procurement outcomes. Officials prioritize avoiding unexpectedly high prices but not seeking low prices. Avoiding winners with prior bad performance is the most important feature. Officials avoid very low competition, while litigation risks and regional favoritism play minor roles. Personal preferences and office interests appear well-aligned among bureaucrats.
Keywords: D73; D90; H11; H57; H83; K41; M54; 330; bureaucrats; public procurement; preferences; conjoint experiments